Biomass yield and nutritive value of sweet lupine in mid altitudes of Lemo District, Hadiya Zone, southern Ethiopia - Tessema, F. (Wolaita Sodo University, 2017)
The study was conducted to determine the biomass yield and nutritive value of sweet lupine varieties in mid altitudes of lemo district, hadiya zone, southern Ethiopia. The study involved a factorial experiment arranged in a randomized complete block design with three replications. The treatments for the study were two sweet lupine varieties (Vitabore (V1) and Sanabore (V2), six levels of Planting spacing (30cmx7cm (S1), 40cmx7cm (S2), 30cmx15cm (S3), 40cmx15cm (S4) 30cmx20cm (S5) and 40cmx20cm (S6) and two locations (Upper gana and Jewe kebeles). Agronomic attributes, yield, chemical composition, and in vitro digestibility values were studied. The data were subjected to analysis of variance and correlation analysis. Sweet lupine varieties in Upper gana kebele gave the highest green forage yield (39.58 t/ha) and forage dry matter (4.84 t/ha) at 30 cm x 7cm planting spacing. Grain yield (GYD) was significantly (P<0.001) affected by location, being 2.98 t/ha at Upper gana, and 2.15 t/ha at Jewe. Vitabor in Jewe kebele gave higher forage DM content (15.63%) while sanabor had higher forage ADF content (38.86 %) in Upper gana kebele. Sweet lupine forage in Jewe kebele gave the highest organic matter (87.01%) and acid detergent fiber (37.50 %) content at stage of 100 % flowering respectively. The effect of location (L), stage of flowering (SF) and planting spacing(S) on sweet lupine forage crude protein (CP) content was highly significant (P < 0.01). Metabolizable energy content of sweet lupine forage was significantly (P < 0.01) affected by both location and stage of flowering. Sweet lupine forage in Upper gana kebele gave the highest CP content (23.11%) while sweet lupine varieties at 50% flowering had the highest forage CP content (23.03%). The highest forage CP content was recorded in sweet lupine which was planted at 40 cm × 20 cm (23.67 %). The highest metabolizable energy content was obtained in Jewe kebele (9.31MJ/kg) and at stage of 100% flowering (9.44MJ/kg). In vitro organic matter digestibility (IVOMD) of sweet lupine forage was highly affected (P < 0.01) by both location (L) and planting spacing (S). Sweet lupine forage gave the maximum in vitro OM digestibility (68.15%) in Upper gana kebele while planting at a spacing of 40x20 cm gave the highest in vitro OM digestibility (69.10%). Sweet lupine grain crude protein (CP) content and in vitro organic matter digestibility (IVOMD) was highly (P<0.01) affected by location. The highest CP (29.11%) content and IVOMD (80.49%) sweet lupine grain recorded in Upper gana kebele.